Procrastination as a protective signal of the survival system: a paradigm shift (Ágora de Heterodoxias, 2026)
The article presents the results of documentary and experiential research aimed at proposing a conceptual reinterpretation of procrastination and how to address it. The starting point was the question: Why, if I know what I have to do, don't I do it? This reflection led to another question: what if procrastination were not the problem, but only a symptom? Changing the perspective led to a review of the literature from another angle, searching for the origin of resistance and defense mechanisms. It was found that the nervous system, in survival mode, responds not only to physical threats, but also to feelings of emotional insecurity. A protective brake is activated in the face of the task, based on the often-unconscious idea that resources are insufficient. This reaction is expressed in the form of procrastination. Based on this finding, an integrative model and intervention methodology are proposed that allow procrastination to be understood as a protective signal and transformed into a conscious response.
Keywords: procrastination; self-efficacy; neuroscience; trauma; emotional regulation